Neural dynamics of adaptive sensory-motor control : ballistic eye movements - Grossberg, Stephen; Kuperstein, Michael (North-Holland, 1986)
This book introduces and develops a quantitative neural theory of a complex sensory-motor system: the saccadic eye movement system.
Advances in psychology ; 30
Keywords: Eye Movements; oftalmologie; Psychomotor Disorders; psychomotorické poruchy; pohyby očí; Saccades; psychologie, klinická psychologie; sakadické oční pohyby